Nanobiorremediação de solo contaminado com pentaclorofenol - Tessaro, Eloisa Fernanda (2018)
Nanobiorremediation is a technique for soil remediation that incorporates two technologies in order to degrade contaminants: nanoremediation through zero valent nano iron (nZVI) and bioremediation through microbial metabolism. The use of nZVI has been shown like an efficient method to degrade organochlorine compounds, which still favors the action of soil microorganisms, making bioremediation possible as a method to remove the residual content of contaminant. Thus, nanoremediation can be used to reduce the initial concentrations of pentachlorophenol (PCP) in order to allow the degradation of residual contents by the bacteria present in the soil, in a more efficient, sustainable and economic way. This work proposes to investigate the nanobioremediation process in residual basalt soil contaminated with pentachlorophenol. PCP is an organochlorine pesticide, considered a soil and water contaminant due to its toxic and carcinogenic character. For this, the maximum tolerable levels of PCP and nZVI were determined by the soil microbiota through the respirometry method. For nZVI none of the concentrations tested had a toxic effect on microbiota. However, for PCP, the concentrations of 3, 10, 20, 50 and 150 mg/kg had a lower CO2 accumulation value than the control, even though at different levels, they had an adverse effect on the microorganisms. In this case, concentrations above 20 mg/kg represented a reduction of more than 50% in total CO2 production relative to the control, generating an unfavorable environment for the microbial activity. Also, we tested variables that influence the soil PCP extraction, such as equipment, solvents and analytical method. It was verified that the procedure of mixing the contaminated soil with methanol and subsequent spectrophotometer analysis with a wavelength of 230nm provided the best values of extraction efficiency. The nanoremediation assay evaluated the required content of nZVI for PCP degradation at levels tolerable by microorganisms for the final nanobioremediation experiment. This concentration was 40 g/kg and allowed to reach a concentration of PCP of 8 mg/kg from the initial content of 20 mg/kg. In the nanobioremediation test, PCP degradation and CO2 production of autoclaved and nonautoclaved soil samples were evaluated in order to differentiate the degradation performed by microorganisms or nZVI. In both cases a degradation of about 40% of the PCP occurred in the first 24 hours, and approached 100% after 60 days of testing. According to the respirometry test, it was possible to observe that an increase in the microbial activity occurred after the degradation of the initial PCP content by the nano iron, signaling potential for biodegradation of the remaining content of the contaminant. The statistical analysis of the data showed that in the time analyzed in this study there was no bioremediation of the PCP, however, there was degradation of about 95% of the contaminant, evidencing that the concentrations and procedures used were satisfactory for soil decontamination.